2011
DOI: 10.2220/biomedres.32.321
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of ciliary beat frequency by ovarian steroids in the guinea pig Fallopian tube: interactions between oestradiol and progesterone

Abstract: Ciliary beat frequency (CBF) was measured in slice preparations of the Fallopian tube fimbria, using videomicroscopy with a high-speed (500 Hz) camera in guinea pigs that were treated with β-oestradiol benzoate (βE 2 B) and medroxy progesterone (mPRG). In non-ovulating guinea pigs at 4 weeks of age, the CBF of the fimbria was high (17.8 Hz). In sexually mature guinea pigs (12-16 weeks of age) with constant ovulation, the CBF varied from 12 Hz to 16 Hz. The in vivo administration of both ICI-182,780 (a blocker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
(45 reference statements)
0
19
0
3
Order By: Relevance
“…Similar to antagonistic effects of estrogen and progesterone towards each other at the endometrial level, it has been suggested that their effects on CBF in the fallopian tube may be nullifying [48]. Considering that the effect of progesterone on ciliated cells is very rapid, it has been suggested that these effects are part of the non-genomic actions of progesterone [49].…”
Section: Ovarian Steroidsmentioning
confidence: 99%
“…Similar to antagonistic effects of estrogen and progesterone towards each other at the endometrial level, it has been suggested that their effects on CBF in the fallopian tube may be nullifying [48]. Considering that the effect of progesterone on ciliated cells is very rapid, it has been suggested that these effects are part of the non-genomic actions of progesterone [49].…”
Section: Ovarian Steroidsmentioning
confidence: 99%
“…The beating of cilia is critical to facilitate the movement of eggs, sperm and the embryo. Estrogen and progesterone can regulate the ciliary beating rate in the reproductive cycle, which ultimately controls the location of fertilization in the fallopian tube and later guides embryo transfer into the uterus (Mahmood et al, 1998;Nakahari et al, 2011). Oviduct-specific glycoprotein 1 [OVGP1], produced by fallopian secretory cells, positively influences the capacitation of sperm and its motility prior to fertilization (Erickson-Lawrence et al, 1989;Verhage et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Our work confirmed that the cultured human fallopian tube epithelium, including ciliated and secretory cells, could be regulated by exogenous steroid hormones secreted by co-cultured ovarian tissues. Specifically, cilia length, cilia-beating status, and oviduct-specific glycoprotein 1 (OVGP1) secretion provided hallmarks of the functional changes in the human fallopian epithelium during the menstrual cycle27282930. In the current study, fallopian explants were incorporated into the Quintet-MFP to facilitate a more complex co-culture environment beyond simple static cultures.…”
Section: Resultsmentioning
confidence: 99%